Increasing Marketing Performance Through Customer Orientation, Competitor Orientation and Product Innovation - Fitri, Maltuf; Nuha, Soya Angga Arifin; Nurudin, Nurudin (Journal of Digital Marketing and Halal Industry, 2022)
The existence of MSMEs plays a very important role in the process of equity and increasing people's income, as well as encouraging economic growth. the existence of fairly tight competition, namely in the economic field, MSMEs are faced with various opportunities and various threats both internally and externally. Most of MSMEs in Semarang City or 73.61 percent admit that they experience difficulties in running their business. In order for MSMEs to survive and get superior marketing performance, MSMEs must understand and understand, and be observant in seeing the market, what consumers want, and what changes must be made in order to be able to compete and survive. This means that companies must innovate in developing their business which is the main strategy in business competition. The purpose of this research is to determine the effect of customer orientation, competitor orientation and product innovation on marketing performance. The number of respondents in this study were 100 respondents who were owners or leaders of MSMEs in Semarang. The research data is in the form of quantitative data with data analysis techniques using Structural Partial Least Squares (PLS-SEM). The results showed that the variable coefficients of customer orientation and competitor orientation had a positive and significant effect on product innovation. The variables of customer orientation, competitor orientation and product innovation have a positive and significant impact on marketing performance. Product innovation variable can mediate positively and significantly between customer orientation and competitor orientation with marketing performance.